2011
DOI: 10.1016/j.apenergy.2011.05.024
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the projected changes in temperature on heating and cooling requirements in buildings in Dhaka, Bangladesh

Abstract: Dhaka, the capital of Bangladesh, is a fast growing megacity with a population of 12.8 million. Due to its tropical location, dense urban morphology and higher than average density of population, buildings in Dhaka are likely to be adversely affected by the projected changes in climate, in particular by the increases in temperature. Buildings play a vital role in most aspects of our lives and their energy consumption patterns affect climate change mitigation and adaptation strategies. It is important to unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 30 publications
0
27
0
2
Order By: Relevance
“…Increases in energy intensive industries and rising energy use from urban buildings are two of the primary reasons for the burgeoning growth in demand for electricity. A relatively high population growth [9], rapid urbanization [10], the lack of suitable land for buildings and increasing urban temperatures due to urban heat island and global climate change [11] are suggested to contribute further to the growing demand. In contrast, annual growth in electricity generation capacity was variable with a range of À1.69 to 25.95% 4 between 2001 and 2011.…”
Section: Energy Infrastructure Development Challengesmentioning
confidence: 99%
“…Increases in energy intensive industries and rising energy use from urban buildings are two of the primary reasons for the burgeoning growth in demand for electricity. A relatively high population growth [9], rapid urbanization [10], the lack of suitable land for buildings and increasing urban temperatures due to urban heat island and global climate change [11] are suggested to contribute further to the growing demand. In contrast, annual growth in electricity generation capacity was variable with a range of À1.69 to 25.95% 4 between 2001 and 2011.…”
Section: Energy Infrastructure Development Challengesmentioning
confidence: 99%
“…Three predominant seasons are present: hot summer from mid-March to mid-June; hot and humid monsoon from midJune to mid-October; and cooler and drier winter season from mid-October to mid-March [10]. Peak occurs during monsoon months, primarily due to high moisture content in the air, with relatively humidity above 90% for most of the time, requiring cooling and hence electricity.…”
Section: Electricity Demand Generation and Shortagementioning
confidence: 99%
“…They showed that properly executed radiant wall panels compared to radiators achieve primary energy savings of 28%. Also, there are many studies about hydronic cooling systems [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%